The Tenuous Grasp: Possession and Loss in the Marketplace. Issue 2 (3rd April 2019) - Redmond, William
Abstract: Generally speaking, markets serve as provisioning mechanisms, facilitating the supply of goods and services to customers. Extensive supply chains with specialist intermediaries create a flow of diverse items to consumers. However, market institutions can also serve as a de-provisioning technology, taking things away from customers. That is, markets can work in reverse. One example is the repossession of a vehicle. The process is often detrimental to low income and minority individuals.